Sawt, Bodies, Species Sonic Pluralism in Morocco - Aubry, Gilles (adocs, 2023)
How do the Moroccan sound archives of the writer Paul Bowles from the 1970s sound today with the musicians of that time? What does an earthquake in Agadir have to do with a Japanese science fiction film? What sound do stones have? And what do we learn about environmental pollution by listening to the agar agar algae? Drawing on critical sound studies, ethnographic research, and artistic practice, this book offers multivoiced narratives about acoustic practices in Morocco. Gilles Aubry's research on the sonic dimensions of our environment, ranges from animal, plant, and mineral voices to ritual practices and technological infrastructures. The Arabic word for these voices in the physical but also in the technological sense is sawt. In collaborations with local musicians, artists and scientists, Aubry explores in experimental settings listening as the basis of "sonic pluralism". The dense descriptions of the multidisciplinary research are complemented by series of photographies. Via QR codes, the text is linked to audiovisual essays and compositions by the artist. The layout of the book takes up this close linking of digital and analog materials.